The effectiveness of antibiotic additives in irrigation fluid used during cataract surgery: A systematic review - Brian Edward Yu; William Herspiegel; Robert Khatib; Jeffrey Thevaranjan; Abbie Lai; Amit X. Garg; Cindy M.L. Hutnik; Monali Malvankar-Mehta (AJO International)
Purpose: To conduct a systematic review investigating the efficacy of antibiotics used in irrigation fluid during cataract surgery on the incidence of post-operative endophthalmitis. Design: Systematic review of literature. Methods: Literature was searched through MEDLINE, EMBASE, CINAHL, ClinicalTrials.gov, and ProQuest Dissertations and Theses until February 17, 2024. Conferences held through the Association for Research in Vision and Ophthalmology and American Academy of Ophthalmology were searched until March 22, 2024. A total of 5341 records were screened leaving 13. One author independently reviewed them for quality and extracted data. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guidelines were followed. Data on the types of antibiotics used, as well as the incidence of post-operative endophthalmitis and complications, were extracted. Results: A total of 608,064 eyes and 566,760 patients were included in the current study. Surgical procedures included phacoemulsification, manual small-incision, and extracapsular extraction. Results showed antibiotic additives reduced postoperative endophthalmitis and bacterial contamination. Vancomycin showed the lowest infection rates, with one study reporting 0 infections out of 220 patients using a concentration of 20 mg/L. Similarly, gentamicin, tobramycin, and cefuroxime also demonstrated reduced infection rates, with gentamicin achieving rates as low as 0.008 % at higher concentrations. Combination therapy with vancomycin and gentamicin further reduced bacterial contamination, with culture positivity rates as low as 2.73 %. In comparator groups without antibiotics, infection rates were significantly higher, ranging from 0.04 % to 0.07 %. No adverse events or complications were reported in those who received antibiotics in their irrigation fluid. Conclusions: Antibiotic additives in irrigation fluid reduce postoperative endophthalmitis and bacterial contamination in cataract surgery. These findings support their inclusion in surgical practice to improve patient outcomes. Based on the current systematic review, the overall quality of evidence is moderate, as findings are supported by a mix of randomized controlled trials and observational studies with some heterogeneity. Further high-quality RCTs are needed to determine optimal antibiotic concentrations and establish standardized guidelines.